2010
DOI: 10.1097/cji.0b013e3181dcd260
|View full text |Cite
|
Sign up to set email alerts
|

Current Experience With CTLA4-blocking Monoclonal Antibodies for the Treatment of Solid Tumors

Abstract: Monoclonal antibodies (mAbs) specific for cytotoxic T lymphocyte-associated antigen 4 (CTLA4) are a novel form of immunotherapy for treatment of patients with advanced cancers. These anti-CTLA4 mAbs prevent normal downregulation of the immune system, thus prolonging and enhancing T-cell activation and potentially promoting an antitumor immune response. Clinical studies in patients with advanced cancers have indicated that CTLA4 blockade with mAbs is associated with antitumor activity in a small percentage of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…It has also been reported that the onset of IRAEs is associated with better clinical outcomes of underlying malignancy (73). However, whether the onset of hypophysitis in patients under anti-CTLA4-mAbs (or a specific grade of this toxicity) may predict better survival and/or response remains to be estimated in further trials with appropriate analytical approach (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that the onset of IRAEs is associated with better clinical outcomes of underlying malignancy (73). However, whether the onset of hypophysitis in patients under anti-CTLA4-mAbs (or a specific grade of this toxicity) may predict better survival and/or response remains to be estimated in further trials with appropriate analytical approach (73).…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the onset of hypophysitis in patients under anti-CTLA4-mAbs (or a specific grade of this toxicity) may predict better survival and/or response remains to be estimated in further trials with appropriate analytical approach (73).…”
Section: Discussionmentioning
confidence: 99%
“…89Y91 In preclinical models, these strategies have been shown to enhance the vaccine-like effect of both chemotherapeutic and radiotherapeutic regimens, thereby constituting promising approaches. 91,79 Gulley and colleagues 92 reported that, in prostate cancer patients, the combination of radiotherapy with an admixture of a recombinant vaccine against prostatespecific antigen (PSA) and B7.1 costimulatory molecules induced a significant increase in PSA-specific and MUC1-specific T cells. The expansion of MUC1-specific T cells indicates that a tumor antigen cross-priming occurs in vivo following radiotherapy.…”
Section: Genetic Background and Clinical Outcomementioning
confidence: 99%
“…However, in this study better survival did not correlate with TKI-induced hypothyroidism. Retrospective analyses suggest that patients who experience immune-related adverse events, including endocrinopathies, may be more likely to benefit from anti-CTLA4-MAb therapy (107,231,232).…”
Section: Why Is It Important To Assess Thyroid Function In Cancer Patmentioning
confidence: 99%